Enhancing satisfaction and word of mouth of young mobile banking users through system quality and individual performance - Duong Luu Thi Thuy; Uyen Nguyen Thi; Quyen Vo Hanh; Nguyet Nguyen Thi My (Cogent Business & Management, 2024)
This study explores the factors that influence Vietnamese mobile banking users' word-of-mouth behavior and sheds light on the impact of customer satisfaction, system quality, and individual performance. The data collected from 297 customers was analyzed through Smart PLS 4.0 utilization. The study findings reveal the direct and significant effect of customer satisfaction on word-of-mouth behavior. In addition, individual performance and mobile banking system quality have been found to be positive factors influencing customer satisfaction. The study also highlights the mediating role of customer satisfaction in the relationship between system quality, individual performance and word-of-mouth, which has not been explored in the prior studies. These results make substantial contributions to the existing literature on signaling theory in business management and hold important policy implications for Vietnamese commercial banks.
Keywords: 650; Individual performance; mobile banking; satisfaction; system quality; word of mouth